Supplementary medial locking plate fixation of Ludloff osteotomy versus sole lag screw fixation: A biomechanical evaluation. (August 2017) - Chatzistergos, Panagiotis E.; Karaoglanis, George C.; Kourkoulis, Stavros K.; Tyllianakis, Minos; Stamatis, Emmanouil D.
Abstract: Background: The Ludloff oblique osteotomy is inherently unstable, which might lead to delayed union and loss of correction. Supplementary fixation to two lag screw fixation has been proposed. The hypothesis is that the osteotomy fixation constructs supplemented by a mini locking plate provide greater resistance to osteotomy gaping and loss of angular correction in response to cyclic loading. Methods: Twenty fourth generation composite 1st metatarsals were used and underwent a Ludloff osteotomy. They were divided in two fixation groups: two lag screws (Group A), and with a supplementary mini locking plate (Group B). Specimens were subjected to either monotonic loading up to failure or to fatigue (cyclic) tests and tracked using an optical system for 3D Digital Image Correlation. Findings: The osteotomy gap increased in size under maximum loading and was significantly greater in Group A throughout the test. This increase was observed very early in the loading process (within the first 1000 cycles). The most important finding though, was that with the specimens completely unloaded the residual gap increase was significantly greater in Group A after only 5000 cycles of loading up to the completion of the test. The lateral angle change under maximum loading was also significantly greater in Group A throughout the test, with that increase observed early in the loading process (5000 cycles). With the specimens completely unloaded the residual lateral angle change was also significantly greater in Group A at the completion of the test. Interpretation: Supplementary fixation with a mini locking plate of the Ludloff osteotomy provided greater resistance to osteotomy gaping and loss of angular correction compared to sole lag screws, in response to cyclic loading. Highlights: A modified fixation for Ludloff osteotomy is proposed utilizing a mini locking plate. Fourth generation composite 1st metatarsals underwent quasi-static monotonic load up to failure or fatigue (cyclic) tests. The specimens were tracked using an optical system for 3D Digital Image Correlation. The developed osteotomy gap was significantly lower in the modified fixation group. The lateral angle change was significantly lower in the modified fixation group.